Intellectual property law and human rights - Torremans, Paul L.C (Information law series, 2020)
[This book] is the expanded edition that provides a complete overview of all the points of interaction between intellectual property and human rights. Once regarded as a niche topic, the nexus of intellectual property and human rights now lies in the eye of the storm that is today's global economy. In this pre-eminent work in the crucial area of legal theory and practice (with nine completely new chapters) authorities in both intellectual property law and human rights law present an in-depth analysis and discussion of essential and emerging issues in the convergence of intellectual property law and human rights law. The fourth edition is fully updated to address current matters as diverse as artificial intelligence, climate change, and biotechnological materials, all centred on the relations between intellectual property and freedom of expression and the fundamental right to privacy in an intellectual property environment"--Provided by the publisher.